(untitled) (Advenimiento, 2022)
This study follows a historical and systematic approach and is presented in two articles. The questions that this study attempts to resolve are: (1) What are the similarities and dissimilarities in the use of the concept of God’s sovereignty in Calvin and Arminius’ view of salvation? (2) What were the historical and theological contexts of the development of these differences? (3) What are some of the implications of these differences for the doctrine of the eschatological judgment?